Most beautiful island - Jones, Jeffery Alan ca. 20. Jh (Bulldog Film Distribution Limited, 2018)
" 'Most Beautiful Island' is a psychological thriller examining the plight of undocumented female immigrants hoping to make a life in New York City. Shot on Super 16mm with an intimate, voyeuristic sensibility, Most Beautiful Island chronicles one harrowing day in the life of Luciana, a young immigrant woman struggling to make ends meet while striving to escape her past. As Luciana's day unfolds, she is whisked, physically and emotionally, through a series of troublesome and unforeseeable extremes. Before her day is done, she inadvertently finds herself a central participant in a cruel game where lives are placed at risk, and psyches are twisted and broken for the perverse entertainment of a privileged few."
Original: USA 2017
Bildformat 16x9 (1.66:1)
Special features: cast & crew interviews
Keywords: Film; DVD-Video